Carbon-based, all-inorganic, lead-free Ag2BiI5 rudorffite solar cells with high photovoltages. (February 2021) - He, Fengqin; Wang, Qian; Zhu, Weidong; Chen, Dazheng; Zhang, Jincheng; Zhang, Chunfu; Hao, Yue
Graphical abstract: Highlights: Carbon-based, all-inorganic, lead-free Ag2 BiI5 solar cell is reported for the first time. The efficiency of Ag2 BiI5 solar cell is improved to 0.71% by air blowing strategy. The solar cell exhibits record-high open-circuit voltage (Voc ) of 0.770 V. Abstract: Lead-free Ag-Bi-I rudorffite materials, such as Ag2 BiI5, have gained ever-increasing attention as potential alternatives to lead halide perovskites for solar cell applications. However, nearly all of rudorffite solar cells are built with a mesoporous structure, which contain instable and expensive hole-transport-layers (HTLs) along with noble metal-electrodes. Herein, carbon-based, all-inorganic Ag2 BiI5 rudorffite solar cell that is free of HTL and noble metal-electrode is reported for the first time. By improving the quality of Ag2 BiI5 film with air blowing recipe, the solar cell with much enhanced efficiency of 0.71% is realized. In particular, it yields an open-circuit voltage (Voc ) of 0.770 V, standing the highest value among Ag2 BiI5 solar cells reported so far. Hence, our work opens the door for developing rudorffite solar cells with simplified fabrication procedures and low cost.